Notai e scrittura a Piacenza: a proposito di notizie dorsali e imbreviature - Mantegna, Cristina (Scrineum, 2013)
The A. picks up the topic wich matters to the historiography of diplomatics in the last two centuries. She reads it again from the point of view of the XI-XII centuries records of Piacenza; they are good examples to reconstruct the events that drove to the achievement of the imbreviaturae case. Notaries in Piacenza were susceptible to the need of giving and warranting fides to the record and they drafted alternatives solutions: each of them is sign of a different phase of the process of definition of the notary’s public role in the medieval legal system.